2012
DOI: 10.1177/014556131209100314
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Helicobacter Pylori and Laryngopharyngeal Reflux in Laryngeal Pathologies

Abstract: We conducted a study to determine the presence or absence of Helicobacter pylori and laryngopharyngeal reflux (LPR) in 43 previously untreated patients who had presented with a laryngeal lesion. Our aim was to determine if there was any association among H pylori, LPR, and laryngeal lesions. H pylori status was determined by real-time polymerase chain reaction (PCR) assays of biopsy tissue obtained during direct laryngoscopy. The presence or absence of LPR was determined on the basis of patients' reflux sympto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 25 publications
0
31
0
Order By: Relevance
“…H. pylori ‐contaminated gastric fluids may reach the UADT in a retrograde fashion and lead to positive PCR results in the UADT. Gastroesophageal reflux and supine position would presumably encourage this phenomenon . This factor could explain the apparent discrepancy with our pilot study, in which we amplified H. pylori DNA by PCR in 38% of the patients testing UADT samples .…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…H. pylori ‐contaminated gastric fluids may reach the UADT in a retrograde fashion and lead to positive PCR results in the UADT. Gastroesophageal reflux and supine position would presumably encourage this phenomenon . This factor could explain the apparent discrepancy with our pilot study, in which we amplified H. pylori DNA by PCR in 38% of the patients testing UADT samples .…”
Section: Discussionmentioning
confidence: 60%
“…H. pylori bacteria may also be detected in the UADT because of gastric contamination . H. pylori ‐contaminated gastric fluids may reach the UADT in a retrograde fashion and lead to positive PCR results in the UADT.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence and severity of LPR was significantly higher in cancer patients than the controls. Furthermore, Cekin et al [52] reported the prevalence of LPR in new patients presenting with a laryngeal lesion was 69.8 % and there was a significant relationship between LPR positivity and presence of a malignant/premalignant laryngeal lesion (p = 0.03). Additional studies examined the direct effect of various individual components of refluxate including acid, pepsin and bile salts on laryngeal cells.…”
Section: Pepsin: Mediator Of Cell Damagementioning
confidence: 98%
“…pylori infection is one of the most common bacterial infections in humans, affecting more than half of the world's population [13] . Its prevalence is 30-40% in developed countries and reaches up to 80-90% in underdeveloped countries [14,15] .…”
Section: Epidemiology and Pathogenesismentioning
confidence: 99%